Аналіз надійності локальної інфокомунікаційної мережі - Лемешко, В. О.; Куренко, В. О. (ХНУРЕ, 2024)
The article analyzes the reliability level of several network topologies. The analysis focused on the impact of the reliability level of individual links and structural redundancy on the probability of fault-free operation of connections between different network switches. The analysis results confirmed that introducing redundancy in the network topology increases information and communication network (ICN) structural reliability. The obtained quantitative results allow us to justify the choice of a particular topology to ensure a given level of structural reliability. Based on the results, it is possible to develop recommendations for choosing a specific network topology depending on the state of the switches, their ports, and the reliability requirements of the ICN in general.
Keywords: локальна мережа; імовірність безвідмовної роботи; імовірність відмови